Effects of systemic Thalidomide and intracerebroventricular Etanercept and Infliximab administration in a Streptozotocin induced dementia model in rats - ELÇİOĞLU, HATİCE KÜBRA; KABASAKAL, LEVENT (ELSEVIER GMBH, 2015)
Tumor necrosis factor-alpha (TNF-alpha) upregulation enhances amyloid beta (AP beta) induced neurotoxicity in Alzheimer's disease (AD). Intracerebroventricular streptozotocin (STZ) administration causes pathological changes and cognitive deficits similar to those seen in AD by causing impairment of brain glucose and energy metabolism. Recent reports indicate a protective role of Thalidomide. Etanercept, and Infliximab, all of which have anti-TNF-alpha activity, against cognitive and neuropathological changes in experimental and clinical studies. We aimed to investigate the protective effects of Thalidomide, Etanercept, and Infliximab in a rat model of intracerebroventricular STZ-induced dementia. Sprague-Dawley rats (250-300 g) were separated to sham (n = 6) and STZ (n = 24) groups. The STZ group was divided into four groups (STZ, STZ-thalidomide, STZ-etanercept, and STZ-infliximab). Morris's water maze (MWM) and passive avoidance (PA) tests were performed. At the end of the third week, brain tissues were obtained. Histopathological analysis, immunohistochemistry, and electron microscopic examinations were done. The improvement performance of the STZ group was significantly reduced in the MWM test (p < 0.001). Compared with the STZ, STZ-thalidomide, STZ-etanercept, and STZ-infliximab groups had significantly better performance (p < 0.001. <0.05 and <0.05, respectively) in the MWM test. STZ administration caused a significant decrease in the mean escape latency in PA reflex (p < 0.001). Thalidomide, Etanercept, and Infliximab were associated with better PA reflexes compared to the STZ group (p < 0.001 for all). Morphological and immunohistochemical results showed increased neurodegenerative changes compared to sham group. Our findings are in line with the findings reported in the literature and encourage further studies with TNF-alpha antagonists, in particular Thalidomide. (C) 2015 Elsevier GmbH. All rights reserved.
Keywords: Streptozotocin; Rat dementia model; Thalidomide; Etanercept; Infliximab; NECROSIS-FACTOR-ALPHA; COGNITIVE IMPROVEMENT; NITRIC-OXIDE; ALZHEIMERS; INHIBITION; MEMORY; DYSFUNCTION; INJECTION; SYNUCLEIN; BETA